Respuesta :

Note:

Your question is a little unclear. But, from my understanding, I assume you may be asking the evaluation of the expression 36x - y when x = 3 and y = -6.

so I will solve based on my assumption which anyways would clear your concept.

Answer:

The value of 36x - y when x = 3 and y = -6 will be: 114

Step-by-step explanation:

Given

Assuming the expression

36x - y

To Determine

Evaluate 36x - y when x = 3 and y = -6

Given the expression

[tex]36x - y[/tex]

substitute x = 3 and y = -6 to evaluate the expression

[tex]36x-y= 36(3) - (-6)[/tex]

            [tex]= 108+6[/tex]

            [tex]= 114[/tex]

Therefore, the value of 36x - y when x = 3 and y = -6 will be: 114